Uma análise narrativa de minha experiência docente em busca do trabalho colaborativo - Lima, Gyzely Suely (2016)
As the teacher-researcher-participant in this study I analysed how occurred my process of attempting to move from my teacher’s practice to live an experience in a collaborative perspective in a classroom. Furthermore, the purpose was to investigate how my conception of collaborative work is reflected in my own practice during the experience of teaching English by using digital technologies. The issues related to it appeared from retelling my stories of my classroom experiences, which made me wonder about my own teaching practice. Thus, some of the following questions guided the research, mainly: a) Which conception of collaboration has been built by myself as a researcher-teacher? b) What are the implications of the conception of collaboration built up by myself in English teaching- learning process? In order to reflect about them, I discuss some of the scholars’ theories related to the concepts of collaboration, such as: Tinzmann; Jones; Fennimore; Bakker; Fine; Pierce (1990), Panitz (1996), Friesen (1997), Wenger (1998, 2006, 2009) Dillenbourg (1999), Magalhães (2002), Magalhães and Celani (2000), Liberalli (2002) and Mello (2012). As my research object is my own experience, the most appropriate methodology to be used was Narrative Inquiry (CLANDININ e CONNELLY, 1998, 2000, 2011). Narrative Inquiry consists in a process of investigation by considering a metaphorical three-dimensional space: personal and social (interaction); past, present, and future (continuity); combined with the notion of place (situation). Clandinin e Connelly (2000, p. 50) explain that “studies have temporal dimensions and address temporal matters; they focus on the personal and the social in a balance appropriate to the inquiry; and they occur in specific places or sequences of places”. The research context was English For Specific Purpose (ESP) classes in an undergraduate course, Logistics, offered by a federal public institution in Minas Gerais, Brazil. There were 15 indirect participants, 4 direct participants, three student-participants and myself as a teacher- researcher-participant. In order to compose the field texts the researching tools I have used: narratives about the experience; stories written by the participants; field notes; and also my lesson plans and the material produced by the participants during the classes. For analysing the research texts I based on principles stated by Ely, Vinz, Downing, Anzul (2001). Throughout this study, I realized how my stories pointed out my tensions related to my binarism and my confusion about conceptions of collaboration. From reflecting, I questioned my own convictions in order to understand how a teacher may build knowledge while seeking for a collaborative work in a classroom. I do believe that these research results may be a bridge between my life stories and the stories of other teachers and researchers by creating the opportunity for reflecting and discussing about building the knowledge of teacher’s practice in a collaborative perspective during the process of teaching and learning English.